2014
DOI: 10.1128/jb.01444-13
|View full text |Cite
|
Sign up to set email alerts
|

A Sporulation Factor Is Involved in the Morphological Change of Clostridium perfringens Biofilms in Response to Temperature

Abstract: Biofilm formation has been associated with bacterial pathogenesis, such as nosocomial and chronic infections, as the resistance of biofilms to environmental stresses has increased. Clostridium perfringens is a Gram-positive spore-forming anaerobic pathogen. This organism survives antibiotic treatment through the formation of biofilms or spores, but the environmental and regulatory factors involved in the biofilm formation remain unclear. Here, we observed that temperature regulates C. perfringens biofilm morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Two different research groups recently showed that treatment of preformed biofilms with proteinase K, cellulose, or DNase I dispersed C. perfringens biofilms, suggesting the presence of proteins, ␤-1,4-linked polysaccharides, and eDNA (49,50). Our studies further demonstrated the presence of eDNA in the supernatant of biofilm cultures acting as a source of DNA to be incorporated into the matrix.…”
Section: Figsupporting
confidence: 53%
See 4 more Smart Citations
“…Two different research groups recently showed that treatment of preformed biofilms with proteinase K, cellulose, or DNase I dispersed C. perfringens biofilms, suggesting the presence of proteins, ␤-1,4-linked polysaccharides, and eDNA (49,50). Our studies further demonstrated the presence of eDNA in the supernatant of biofilm cultures acting as a source of DNA to be incorporated into the matrix.…”
Section: Figsupporting
confidence: 53%
“…Furthermore, incubation at 37°C, but not at 25°C, upregulated levels of pilA2 mRNA, which encodes the main pilin subunit of the matrix-associated C. perfringens TFP (50). These data suggest that C. perfringens biofilms are differentially regulated.…”
mentioning
confidence: 54%
See 3 more Smart Citations